Searching for Best Direction in Healthcare: Distilling Opportunities, Priorities and Responsibilities - Terrence Montague, Amédé Gogovor, Lucas Marshall, Bonnie Cochrane, Sara Ahmed, Emily Torr, John Aylen and Joanna Nemis-White (Healthcare Quarterly, 2016)
Canada's health and its care are evolving. Evidence from serial Health Care in Canada surveys of the public and health professionals over the last two decades reveal a persistent sense of care quality, despite an aging population, decreasing levels of good and excellent health, increasing prevalence of chronic illnesses; and sub-optimal access to timely and patient-centred care. Stakeholders are, however, somewhat pessimistic and many sense complete rebuilding, or major changes, may be necessary. To improve access, the primary health concern of all Canadians – increasing medical and nursing school enrolment, and requiring professionals to work in teams – have attracted increasingly high support from both the public and professionals. However, physicians' support lags behind that of nursing, pharmacy and administrative colleagues; and, currently, only a minority of patients and professionals are actively involved in team care programs. Another example in which high levels of support may not necessarily translate into priority implementation of promising interventions is the realm of patient-centred care. The public and all professionals report a very high level of general support for care provided in a caring and respectful manner. However, while the public rank it second in implementation priority, following timely access, the majority of professionals rank it only fourth. By contrast, there is remarkable pan-stakeholder concordance around interventions to improve the overall health system, with the majority of public and professional stakeholders rating the creation of national supply systems as their top priority to expedite the clinical and cost efficiency of new treatments. There is a similar pan-stakeholder concordance around priority of responsibility to drive innovations, the top three being: federal/provincial governments; research hospitals/regional health authorities; and the pharmaceutical industry. In summary, Canadians are at a healthcare crossroads. Population health is decreasing, chronic diseases are increasing and desire for timely access to patient-centred, team-delivered and technology-supported care remain top concerns. Despite some disconnects between theoretical support for, and priority to implement, promising innovations, there is universal support to optimize resources to make things better. And there is concordance around the leadership best suited to lead innovation. Things can be better.
Keywords: stakeholder survey, quality of care, healthcare transformation